Developing Eco-Religious Literacy through Islamic Environmental Discourse: Language Skills, Public Ethics, and Sustainable Communities - Saepudin; Suhartina Suhartina (LPPM IAIN Parepare, 2026)
This article examines the contestation of theocentric and secular paradigms in global environmental ethics by positioning Islamic environmental ethics as a critical-conceptual lens. The background of the study is based on the fact that the global ecological crisis is not only caused by weak technology or policies, but also by a paradigm crisis in understanding the relationship between humans, nature, and values. This article uses qualitative methods with a library study design and document analysis. Data are analyzed through literature reduction, thematic categorisation, critical interpretation, and conceptual synthesis of sources on Islamic environmental ethics, the secular paradigm, environmental jurisprudence, ecological education, Green Deen, Green Madrasa, Al-Mizan, and Islamic sustainability instruments. The results show that the secular paradigm contributes to environmental regulation, science, and governance, but tends to be reductionist when nature is understood solely as an object of policy and economics. In contrast, the theocentric paradigm of Islam offers an ethical foundation through tawhid, khalifah, amanah, mizan, and verses of kawniyah. This study emphasises the need to develop a global environmental ethics through a critical dialogue between scientific rationality and spiritual responsibility.